2017
DOI: 10.1088/1361-6587/aa8a54
|View full text |Cite
|
Sign up to set email alerts
|

Structured targets for advanced laser-driven sources

Abstract: Structured targets offer great control over ultra-intense laser-plasma interaction, allowing the optimization of laser-target coupling for specific applications. By means of particle-in-cell simulations we investigated three applications in particular: high-order harmonic generation (HHG) with grating targets, enhanced target coupling with multilayer targets and the generation of intense laser-driven terahertz (THz) pulses with structured targets. The irradiation of a solid grating target at the resonance angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Novel interaction conditions and target configurations have been constantly explored [8] . Recently, structured targets have been intensively studied as it was shown that they are able to enhance the level of laser light absorption [9] and the radiation yield (HHG, THz, X-ray) [10,11] or to improve the physical parameters of electron and ion beams via excitation of surface plasmons (plasma waves) [12][13][14] . Surface plasma waves (SPWs) are localized electron oscillation modes that can be excited at the vacuum-plasma interface by a laser Correspondence to: M. Cerchez, Institut für Laser und Plasmaphysik, Heinrich-Heine Universität Düsseldorf, Universitätsstr.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel interaction conditions and target configurations have been constantly explored [8] . Recently, structured targets have been intensively studied as it was shown that they are able to enhance the level of laser light absorption [9] and the radiation yield (HHG, THz, X-ray) [10,11] or to improve the physical parameters of electron and ion beams via excitation of surface plasmons (plasma waves) [12][13][14] . Surface plasma waves (SPWs) are localized electron oscillation modes that can be excited at the vacuum-plasma interface by a laser Correspondence to: M. Cerchez, Institut für Laser und Plasmaphysik, Heinrich-Heine Universität Düsseldorf, Universitätsstr.…”
Section: Introductionmentioning
confidence: 99%
“…− λ L /λ g for q = 1. The electron acceleration by the evanescent field of an SPW has been theoretically and experimentally investigated [12,[17][18][19][20][21] , and the studies demonstrate that the SPW excitation for the resonant condition has a direct impact on the electron acceleration process leading to improved physical parameters such as enhanced flux and charge density of the electrons, a higher electron maximum energy, and a higher absorption efficiency [14,[21][22][23] . Moreover, in the resonant regime, SPWs are a very efficient route to transfer the laser energy via hot electrons to secondary sources including high harmonic generation [24] or ion acceleration [25] and to optimize the physical properties of these sources [13,17,22,23,25,26] .…”
Section: Introductionmentioning
confidence: 99%
“…These results emphasize the robustness of the acceleration mechanism and encourage the development of a compact electron source at few MeV of energy, with potential applications for ultra-fast electron diffraction, 20,21 photo-neutron generation, 22 or enhanced emission of THz radiation. 23…”
Section: Introductionmentioning
confidence: 99%
“…The low-density layer can either be a controlled pre-plasma or a solid nanostructured material with ultra-high void fraction. Both solutions allow for a high absorption efficiency of the laser energy by the hot electrons population, which results into more ions accelerated at higher energies with respect to a simple flat foil [55][56][57]. Nevertheless, pre-plasmas-usually generated via target pre-expansion induced by the laser pedestal or ns-duration pulses [58, 59]-is affected by poor stability and control, since large deviations may arise depending on the specific laser facility.…”
mentioning
confidence: 99%